Low Mood Leads to Increased Empathic Distress at Seeing Others’ Pain - Cao, Yuan; Dingle, Genevieve; Chan, Gary C. K.; Cunnington, Ross (Frontiers in Psychology, 2017)
Previous studies have shown changes in empathy in patients with depression, including an elevated level of trait personal distress. This study examined if low mood causes changes in self-reported empathic distress when seeing others in pain. To test this, we conducted an initial (n = 26) and close replication study (n = 46) in which sad mood was induced in healthy participants (overall mean age M = 21, SD = 5, range = 18-41 years). Participants viewed and rated video stimuli inferring pain experienced by other people. Results showed that participants perceived the videos depicting others’ pain (versus no-pain) to be more distressing under a sad mood compared to a neutral mood condition, implying that sadness enhances one’s emotional reactivity towards others’ distress. This supports previous depression literature suggesting an impaired emotional processing ability, and could contribute to some of the unhelpful behaviors seen in depression such as social withdrawal and avoidance.